PENGARUH KESADARAN, KUALITAS PELAYANAN, PEMERIKSAAN DAN SANKSI PERPAJAKAN PADA KEPATUHAN WAJIB PAJAK RESTORAN - Meindra Jaya, Ida Bagus; Jati, I Ketut (E-Jurnal Akuntansi; Vol 16 No 1 (2016), 2016)
This research aims to determine how the influence of the taxpayer awareness, quality of service, tax audits and tax penalties on tax compliance in paying taxes restaurants Revenue in Denpasar. The theory used is the theory hearts Research husband legitimacy. The data used in this study are primary data by distributing 100 questionnaires to taxpayers registered in Denpasar Revenue Service. The data analysis technique used in this research is multiple linear regression. Based on the analysis, it is known that variable taxpayer awareness, quality of service, tax audits and tax penalties positive effect on tax compliance restaurants Revenue Service Denpasar.
Keywords: awareness of taxpayers, quality of service, audits, tax penalties